2023
DOI: 10.1001/jamanetworkopen.2022.53952
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Consumer Complaint Investigation Scores, Recertification Survey Scores, and Overall Nursing Home Health Inspection Star Quality Rating

Abstract: ImportanceThe Centers for Medicare & Medicaid Services’ Five-Star Quality Rating System combines results from nursing home recertification surveys and complaint investigations into a single indicator for health inspections. This combination may mask complaint investigation results.ObjectiveTo construct and compare star ratings specific to recertification surveys and specific to complaint investigations to discern whether they provide different information.Design, Setting, and ParticipantsIn this qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A complaint results in no deficiencies (zero-deficiency complaints [ZDCs]) when 1) the complaint allegations are determined to be unsubstantiated, that is, not being valid, 2) the complaint is valid, and hence substantiated but complaint investigators are unable to find evidence of a regulatory violation, and 3) the complaint is substantiated but involves an issue that is not addressed in the federal regulations (see Figure 1; Peterson & Bowblis, 2023). The purpose of this paper is to examine the second and third scenarios above: complaints that are substantiated but do not yield deficiencies (referred hereafter as zero-deficiency substantiated complaints [ZDSCs]).
Figure 1.Schematic diagram of complaint investigation process.Note: SSA: state survey agency; NH: nursing home.
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A complaint results in no deficiencies (zero-deficiency complaints [ZDCs]) when 1) the complaint allegations are determined to be unsubstantiated, that is, not being valid, 2) the complaint is valid, and hence substantiated but complaint investigators are unable to find evidence of a regulatory violation, and 3) the complaint is substantiated but involves an issue that is not addressed in the federal regulations (see Figure 1; Peterson & Bowblis, 2023). The purpose of this paper is to examine the second and third scenarios above: complaints that are substantiated but do not yield deficiencies (referred hereafter as zero-deficiency substantiated complaints [ZDSCs]).
Figure 1.Schematic diagram of complaint investigation process.Note: SSA: state survey agency; NH: nursing home.
…”
Section: Introductionmentioning
confidence: 99%
“…Several research studies have been conducted in the last few years considering NH deficiencies as overall quality measures (Alexander & Madsen, 2017; Harrington et al, 2016; Lerner et al, 2014). Research has also examined the role of complaints in quality assessment (Bhattacharyya et al, 2023b; Peterson & Bowblis, 2023; Troyer & Sause, 2011) and the changing number of complaints over the past several decades (Hansen et al, 2019; Peterson et al, 2020). Stevenson was among the first to use NH complaints to estimate the quality of NH care; he reported that 35% of NHs had no complaints, and 18% had five/more complaints during 1998–2002 (Stevenson, 2006).…”
Section: Introductionmentioning
confidence: 99%